(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The cement and concrete industries are huge. What doesthis mean in terms of the environment? Concrete and other cementationsmaterials have both environmental advantages and disadvantages. Current environmental and economic circumstancesaccelerate the developments of new concrete constituents. Whereas the processtechnology impacts the mix-design strategy, it seems obvious that manufacturingprocess is prone to evolutions. This article presents a method to compareenvironmental and economic consequences of different technological solutions onthe basis of the influence on the cement consumption needed for a givenconcrete performance. Case study is the choice of dry batch or central mixedconcrete production systems for a ready mixed concrete production. Thetheoretical difference in cement consumption is estimated by considering thatthe water content fluctuation is by far the dominant factor governing the truckto truck variation. The addition of a mixer is effectively found to contributeto cement reduction. Environmental comparison is performed using an EADTindicator (Environmental Amortization Duration Time) defined in the article,and testing various environmental data. The EADT for energy consumption,released CO2 and particles are found below 6 years, in the whole range oftested environmental data for an annual production of 40,000 m3 yr_1, with 2 m3mixer for the central mixed concrete plant. The NOx and SO2 EADT results arefound sensitive to the releases of the steel plant. The financial amortizationduration time corresponding to the purchase of a mixer, is found less than 2years. Although the chosen application case is simplified, these resultsencourage further research. Environmental impact of building products consists ofprocurement of raw material, manufacture items (raw materials and product) andalso the use of energy resources during transportation – all of which burdenthe environment. Environmental burdens of concrete and concrete productsconsist of limestone quarrying, burning and grinding of clinker, extraction,excavation and crushing of cement stone materials, manufacturing andtransportation of raw materials and the final product. The environmentalburdens of concrete, hollow-core slabs, roofing tiles, exterior wall panels,concrete beams and columns are dealt with in the assessment. The differences in environmental burdens between variousconcrete products are a consequence of different binder contents and types,long transportation distances of raw materials and products and differentelectricity consumption especially in the production phases. Environmentalimpacts in the material manufacturing and construction stages of a retainingwall using precast concrete with a revegetation function and a retaining wallplaced in situ with ready-mixed concrete were compared. The retaining wallusing precast concrete was constructed by piling hollow precast concrete boxesof which hollows were filled with soils emitted in the construction site.